The Dynamics of labor Migration Disguised Human Trafficking in North Wollo, Ethiopia: A Pre-Departure Vulnerability Context to Human Trafficking. - Asfaw, Mulugeta Berihun (Italian Sociological Review, 2018)
Abstract The migration of economically and socially vulnerable Ethiopian men, women and children has become a mounting phenomenon. Although their dislodgment is usually disguised with labor migration, their vulnerable position makes them easy targets for traffickers. This study investigated the pre departure vulnerability contexts that render individuals to human trafficking in North Wollo, Ethiopia. Utilizing mixed research approach information was gathered from various groups of purposively selected informants: returnees, law enforcing agent, knowledgeable key informants and prosecuted local trafficker. In-depth interview, key informant interview, survey, FGDs and documentary review were used as the principal means of generating data. The study disclosed that women, youths, unemployed, early married, Muslim and those with low educational profile are found to be more vulnerable to human trafficking than their counter parts. The finding of the study also uncovered that, individuals are found highly pressured by poverty and various socio cultural forces; ever growing materialism, social pressure and better life syndrome, the culture of migration, peoples growing pessimism on conventional means of success like education, early marriage, gender discrimination and changing gender role; to consider migration as the only viable means of success which ultimately made them fall prey to traffickers.